Working women and breast cancer: state of the evidence - The Breast Cancer Fund, San Francisco; Engel, Connie L.; Rasanayagam,Sharima M. (San Francisco, 2015)
"Which occupations, and which exposures on the job, put women at greatest risk for breast cancer? What can we do to protect workers and prevent the disease? Our new report entitled Working Women and Breast Cancer: State of the Evidence, uncovers elevated breast cancer risk for working women. A first of its kind review, the report uncovers more than 20 occupations associated with considerably increased risk of breast cancer compared to the risk for the general population, including nurses, teachers, first responders and more. We are confident that there is a better way forward, and that a cancer-free economy is within our grasp. The report offers recommendations for research and policies that prioritize workers’ health over industry profit or political gains."